IDENTITY NEGOTIATION OF CHRISTIAN AND MUSLIM STUDENTS IN INTERACTION BETWEEN RELIGIONS IN LANGSA - Mawardi Mawardi; Yusmami Yusmami; Muhammad Suhaili Sufyan; Azwir Azwir (State Islamic University North Sumatra, 2019)
Abstract: This article describes how negotiation between the Christian and Muslim students in public place at Langsa. The objectives of the study are twofold, namely: the reason of Christian students deciding Langsa as the place of study despite different social condition from their own place and the pattern of negotiation conducted by the Christian students. Negotiation identity theory and national choice theory are used to know the reason of Christian students pointing Langsa as the place of study. using qualitative method with the phenomenal approach, it is found that the tolerance and harmony interaction between Christian and Muslims student in public place at Langsa. The pattern of negotiation used in public place at Langsa is: functional biculturalism that respect the different identity. this pattern is more effective to gain the culture shock and get the interaction easily the Christian and Muslim students in public place at Langsa.Abstrak: Negosiasi Identitas Mahasiswa Kristen dengan Muslim dalam Interaksi antar Agama di Kota Langsa. Tulisan ini menjelaskan pengalaman mahasiswa Kristiani bernegosiasi dengan mahasiswa Muslim dalam ruang publik di Langsa. Mendasarkan pada ruang sosial yang berbeda dengan kondisi mahasiswa Kristiani, pembahasan dimaksudkan untuk mengungkap alasan mahasiswa Kristiani memilih kuliah di Langsa yang berbeda kondisi sosial dengan daerah asalnya. Dengan menggunakan metode kualitatif dan pendekatan fenomenologis, didapatkan sebuah gambaran interaksi yang toleran antara mahasiswa Muslim dan Kristiani dalam ruang publik di Langsa. Adapun bentuk pola negosiasi yang dilakukan dalam ruang publik yaitu bikultarisme fungsional dengan menghargai identitas yang berbeda dengan aktor. Pola ini dianggap lebih efektif untuk menyelesaikan keterkejutan terhadap budaya baru dan memudahkan berinteraksi mahasiswa Kristiani dan Muslim dalam ruang publik di Langsa.Keywords: negotiation, identity, interaction, Muslim, Christian, public place